Paleoenvironmental reconstruction and hydrocarbon potentials of Upper Cretaceous sediments in the Anambra Basin, southeastern Nigeria - Adebayo, O.F. (Elsevier B.V., 2018)
Palynological, organic petrographic, and organic geochemical analyses of the Campanian-Maastrichtian sediments in Akukwa-2 well were carried out to infer their paleoenvironments, origin of the organic matter, and hydrocarbon generation potentials. The TOC values of the analysed sediments range from 0.27â3.02 wt, while the S2 pyrolysis yield range from 0.55 to 3.35 mg HC/g rock. This indicates that the Nkporo and Mamu sediments possess fair source generative potential. The samples contain Type III-II and Type III kerogen as shown by the present-day HI values between 58 and 292 mg HC/g TOC and pyrolysis-GC data. The organic matter within the sediments is also likely to generate mainly gas. This is in agreement with the petrographic observations, which revealed that the analysed shale samples contain abundant vitrinite macerals, apart from bituminite, alginite, cutinite, and resinite. Also, the sediments are immature to early mature in terms of hydrocarbon generation as indicated by vitrinite reflectance, biomarker maturity, and pyrolysis Tmax data. Biomarker distribution ratios, palynomorphs assemblage, and organic petrographic observations further point out that the organic materials within the sediments were of mixed aquatic and terrigenous origin and were deposited under suboxic paleodepositional conditions. Based on sedimentological, palynological, and biomarker characteristics, the environment of deposition of the analysed sediments was inferred to be a relatively quiet, shallow marine with fluvial incursion, most especially at the upper part of the intervals studied and consequently, it is a delta associated depositional environment with a fluviatile influence. The sediments are therefore suggested to be deposited in a paleogeographic setting close to vegetation source. Â© 2018 Elsevier B.V.